The two points on the line is (0,-1) and (3,-6).
Use the slope intersept form to calculate the equation of the line.
![y-y1=(y2-y1)/(x2-x1)(x-x1)](https://img.qammunity.org/2023/formulas/mathematics/college/j2apttnrmaulxeubwzr25wplepkb41utk7.png)
Put these points in the equation implies,
![\begin{gathered} y+1=(-6+1)/(3-0)(x-0) \\ y+1=(-5)/(3)x \\ 3y+3=-5x \\ 3y+5x+3=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j4gg73mb5zrprijcbsamxkomax84bivwx1.png)
Therefore, the equation of the line is 3y+5x+3=0.
Consider the second line, the points are (0,-2) and (1,0).
![\begin{gathered} y+2=(0+2)/(1-0)x \\ y+2=2x \\ y=2x-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qv45ukgbqjclzk1b1h07ajxbjsz6unt4lm.png)
Thus, the equation of the line is y=2x-2.
Consider the third line, the points are (0,1) and (-3,6).
![\begin{gathered} y-1=(6-1)/(-3-0)x \\ y-1=-(5)/(3)x \\ y=-(5)/(3)x+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ipi2nkg5azsqcl7um407fvtwsa30gs3g84.png)
Thus, the equation of the line is y=-(5/3)x+1.